2008
DOI: 10.1007/s00246-008-9284-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Left Ventricular Pacing Preserves Left Ventricular Function in Children

Abstract: Chronic right ventricular (RV) pacing can induce structural and functional cardiac deterioration. Because animal studies showed a benefit of left ventricular (LV) over RV pacing, this study compared the effects of chronic RV and LV pacing in children. Retrospectively, echocardiographic data were evaluated from 18 healthy children (control subjects) and from children undergoing chronic epicardial RV pacing (7 RVP) or LV pacing (7 LVP). Assessment included LV end-diastolic wall thickness (LVEDWT) and end-systoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 44 publications
5
29
0
3
Order By: Relevance
“…This study strongly supports previous findings of a retrospective pediatric report 7 showing a decrease in LV function specifically due to RV free wall pacing. Our results also confirm data on preservation of LV function with LV apical or LV lateral wall pacing, [10][11][12][13][14] including a large retrospective pediatric multicenter survey 8 and a recently published experimental study. 22 Our present report does not show any superiority of RV septal over RV apical pacing.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study strongly supports previous findings of a retrospective pediatric report 7 showing a decrease in LV function specifically due to RV free wall pacing. Our results also confirm data on preservation of LV function with LV apical or LV lateral wall pacing, [10][11][12][13][14] including a large retrospective pediatric multicenter survey 8 and a recently published experimental study. 22 Our present report does not show any superiority of RV septal over RV apical pacing.…”
Section: Discussionsupporting
confidence: 88%
“…9 Pediatric pacemaker therapy represents an optimal model for the evaluation of the long-term effects of different pacing sites because, on the basis of surgical preferences and in contrast to adults, various pacing sites are used, including LV epicardial pacing. In small single-center reports [10][11][12][13][14] and a larger retrospective survey, 8 pacing from the LV apex or free wall was associated with better preservation of LV function. The purpose of the present multicenter study was to evaluate the influence of different ventricular pacing sites on long-term LV function in children with nonsurgical atrioventricular block and a structurally normal heart and to search for a mechanism for the difference in pump function between sites by measuring mechanical synchrony and efficiency in a cross-sectional echocardiographic evaluation.…”
Section: Circulationmentioning
confidence: 89%
“…3,4 Experimental and clinical studies indicate that LV pacing sites often render better hemodynamic performance than RV pacing sites. [5][6][7] In a previous acute canine study, we observed hemodynamic benefits by LV septal and LV apical pacing, compared with RV apical pacing, and mixed effects during RV septal pacing. 8 No studies have directly addressed the influence of alternate site pacing on myocardial efficiency.…”
Section: Clinical Perspective On P 579mentioning
confidence: 83%
“…However, statistical testing on many variables may lead to Type I errors (falsely positive significant differences), despite correction for multiple comparisons. Despite these potential differences, adverse hemodynamic effects of RV pacing are equally clear in the human 5,7,28 and canine heart. 8,29 Maintaining conduction, contractile coordination, and LV pump function as close as possible to that during normal conduction, as demonstrated for LV septal and LV apical pacing over 4 months, may decrease the long-term risk of developing heart failure.…”
Section: Limitations and Potential Clinical Implicationsmentioning
confidence: 99%
“…O tratamento desta condição tem sido feito com o uso de medicamentos, pela ressincronização cardíaca e menos comumente por transplante cardíaco 27,50,51 A influência da miocardite intrauterina provocada pelos autoanticorpos maternos, já previamente discutida, é considerada pela literatura como o fator mais importante para a evolução tardia desfavorável dos portadores de bloqueio AV congênito 5,6,71,76,77 . O motivo para a realização deste estudo é porque alguns pacientes portadores de marcapasso cardíaco podem apresentar insuficiência cardíaca (diminuição na força do coração), necessitando de tratamento com medicamentos e até mesmo trocar o tipo de marca-passo.…”
unclassified